A Novel Pathogenic Variant in the SCA25-Related Gene Expanding the Etiology of Early-Onset and Progressive Cerebellar Ataxia in Childhood - Ferrera, Giulia; Izzo, Rossella; Ghezzi, Daniele; Nanetti, Lorenzo; Lamantea, Eleonora; Ardissone, Anna (Neuropediatrics, 2024)
Spinocerebellar ataxias (SCAs) are heterogeneous autosomal dominant progressive ataxic disorders. SCA25 has been linked to PNPT1 pathogenic variants. Although pediatric onset is not unusual, to date only one patient with onset in the first years of life has been reported. This study presents an additional case, wherein symptoms emerged during the toddler phase, accompanied by the identification of a novel PNPT1 variant. The child was seen at 3 years because of frequent falls. Neurological examination revealed cerebellar signs and psychomotor delay. Brain MRI showed cerebellar atrophy (CA), cerebellar cortex, and dentate nuclei hyperintensities. Metabolic and genetic testing was inconclusive. At follow-up (age 6), the child had clinically and radiologically worsened; electroneurography (ENG) revealed axonal sensory neuropathy. Screening of genes associated with ataxias and mitochondrial disease identified a novel, heterozygous variant in PNPT1, which was probably pathogenic. This variant was also detected in the proband's mother and maternal grandmother, both asymptomatic, which aligns with the previously documented incomplete penetrance of heterozygous PNPT1 variants. Our study confirms that SCA25 can have onset in early childhood and characterizes natural history in pediatric cases: progressive cerebellar ataxia with sensory neuropathy, which manifests during the course of the disease. We report for the first time cerebellar gray matter hyperintensities, suggesting that SCA25 should be included in the differential diagnosis of cerebellar ataxias associated with such brain imaging features. In summary, SCA25 should be considered in the diagnostic workup of early onset pediatric progressive ataxias. Additionally, we confirm an incomplete penetrance and highly variable expressivity of PNPT1-associated SCA25.
Keywords: PNPT1; SCA25; progressive ataxia; childhood ataxia